Edukasi Kewirausahaan tentang Pentingnya Adaptasi Digital dan Legalitas Usaha di Kelurahan Bantargebang, Bekasi - Della Arianni Syafitri; Fitri Wulandari; Novi Fitria Hermiati; Zulfa Zakiatul Hidayah (Jurnal Informasi Pengabdian Masyarakat, 2024)
There is no doubt that micro, small and medium enterprises (MSMEs) have become an important part of the Indonesian economy. However, they still face several challenges, such as not having a business legality and a lack of ability to take advantage of online sales opportunities. This study aims to identify the elements that influence the growth of MSMEs, with an emphasis on the importance of business legality and the use of social media for online sales. The approach using socialization to the community is used to provide an understanding of the benefits of business legality and online sales strategies. The results of the study indicate that having a business legality can provide better access to government guidance and bank credit. entrepreneurship education in Bantargebang Village, Bekasi City, which emphasizes the importance of digital adaptation and understanding business law Alignment of technology in the digital era.